Early Treatment Initiation With Oral Prednisolone for Relapse Prevention Alleviates Depression and Fatigue in Aquaporin-4–Positive Neuromyelitis optica Spectrum Disorder - Akaishi, Tetsuya; Takahashi, Toshiyuki; Fujihara, Kazuo; Misu, Tatsuro; Fujimori, Juichi; Takai, Yoshiki; Nishiyama, Shuhei; Abe, Michiaki; Ishii, Tadashi; Aoki, Masashi; Nakashima, Ichiro (Frontiers in Neurology, 2021)
Background: Neuromyelitis optica spectrum disorder (NMOSD) is a relapsing autoimmune-related neurological disorder in the central nervous system. Most patients with NMOSD have serum anti-aquaporin-4 immunoglobulin G antibodies (AQP4-IgG). In addition to optic neuritis and myelitis, other insidious symptoms such as depressive state and chronic fatigue in NMOSD are gradually being recognized. Methods: To elucidate the impact of low- to medium-dose oral prednisolone (PSL) as a relapse prevention therapy for psychiatric disturbances and chronic fatigue in NMOSD, we evaluated the clinical data from 39 patients with AQP4-IgG-positive NMOSD, along with the details of present and cumulative oral PSL dosage. Results: Thirty-six of the 39 patients were presently treated with low- to medium-dose oral PSL, and the mean and standard deviation of the present daily dose of oral PSL was 7.9 ± 4.0 mg/day. None of the patients were treated with a daily PSL dose of >15 mg. As a result, the disease duration and the untreated period before starting oral PSL showed weak to moderate correlations with the subsequent severities of psychiatric disturbance and fatigue level. Meanwhile, none of the evaluated other treatment-related variables, such as the present oral PSL daily dose, cumulative PSL dose, months of oral PSL administration, previous courses of steroid pulse therapy, and co-administered immunosuppressants, were correlated with these insidious symptoms. Conclusion: Our results suggest that the use of long-term low- to medium-dose oral PSL ≤15 mg daily for relapse prevention in AQP4-IgG-positive NMOSD would not aggravate the psychiatric and fatigue conditions. On the contrary, early initiation of oral PSL for relapse prevention, together with significantly decreased relapse rate, alleviated the subsequent depressive state and fatigue in the disease.